2022
DOI: 10.1177/00302228221102687
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of the Inventory of Complicated Grief

Abstract: The aim of this study was to investigate the psychometric properties of the Persian version of the Inventory Complicated Grief (ICG) including reliability, validity and factorial structure. In this cross-sectional study, 332 women and men bereaved at least 6 months from the adult population of Iran. The results showed Cronbach’s alpha was found to be 0.94 for the scales overall score. Inventory Complicated Grief found a positive and significant correlation between the beck depression inventory (BDI) (r = .62, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The adult hope scale was used to assess divergent validity. According to the results, hope was negatively related to grief due to the loss of Covid-19, which is similar to studies that have shown that people with lower hope experience more severe symptoms of more complicated grief (Ludwikowska-Świeboda & Lachowska, 2019;Yousefi et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…The adult hope scale was used to assess divergent validity. According to the results, hope was negatively related to grief due to the loss of Covid-19, which is similar to studies that have shown that people with lower hope experience more severe symptoms of more complicated grief (Ludwikowska-Świeboda & Lachowska, 2019;Yousefi et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Promoting professional support during these stages might manage these concerns and their associated distress (Peñacoba‐Puente et al., 2011). In Iran, most of the studies on pregnancy concerns have a quantitative design (Kordi et al., 2015; Yousefi, 2015). Quantitative research in understanding the context in which people live is weak (Creswell & Plano Clark, 2018).…”
Section: Introductionmentioning
confidence: 99%